Discussion about suitable applications for biodegradable plastics regarding their sources, uses and end of life. (15th February 2023) - Paul-Pont, Ika; Ghiglione, Jean-François; Gastaldi, Emmanuelle; Ter Halle, Alexandra; Huvet, Arnaud; Bruzaud, Stéphane; Lagarde, Fabienne; Galgani, François; Duflos, Guillaume; George, Matthieu; Fabre, Pascale
Highlights: - Biodegradable plastics are relevant for selected applications. - Better certification and clearer instructions are needed to improve waste management. - Methodological limits hamper the evaluation of plastic biodegradability and toxicity. - Considering the environment as a waste treatment system is not acceptable. Abstract: This opinion paper offers a scientific view on the current debate of the place of biodegradable plastics as part of the solution to deal with the growing plastic pollution in the world's soil, aquatic, and marine compartments. Based on the current scientific literature, we focus on the current limits to prove plastic biodegradability and to assess the toxicity of commercially used biobased and biodegradable plastics in natural environments. We also discuss the relevance of biodegradable plastics for selected applications with respect to their use and end of life. In particular, we underlined that there is no universal biodegradability of plastics in any ecosystem, that considering the environment as a waste treatment system is not acceptable, and that the use of compostable plastics requires adaptation of existing organic waste collection and treatment channels.